Magnetic resonance microimaging of the spinal cord in the SOD1 mouse model of amyotrophic lateral sclerosis detects motor nerve root degeneration - Cowin, G.; Butler, T.; Kurniawan, N.; Watson, Charles; Wallace, R. (Academic Press, 2011)
Amyotrophic lateral sclerosis (ALS) is characterized by selective degeneration of motor neurons. Current imaging studies have concentrated on areas of the brain and spinal cord that contain mixed populations of sensory and motor neurons. In this study, ex vivo magnetic resonance microimaging (MRM) was used to separate motor and sensory components by visualizing individual dorsal and ventral roots in fixed spinal cords. MRM at 15 μm in plane resolution enabled the axons of pure populations of sensory and motor neurons to be measured in the lumbar region of the SOD1 mouse model of ALS. MRM signal intensity increased by 38.3% (p<0.05) exclusively in the ventral motor nerve roots of the lumbar spinal cord of ALS-affected SOD1mice compared to wild type littermates. The hyperintensity was therefore limited to white matter tracts arising from the motor neurons, whereas sensory white matter fibers were unchanged. Significant decreasesin ventral nerve root volume were also detected in the SOD1 mice, which correlated with the axonal degeneration observed by microscopy. These results demonstrate the usefulness of MRM in visualizing the ultrastructure of the mouse spinal cord. The detailed 3D anatomy allowed the processes of pure populations of sensory and motor neurons to be compared.